KONTRIBUSI ILMU TAFSIR/HADIS DALAM PEMBANGUNAN KARAKTER BANGSA - Mustamin Arsyad (Jurnal Studia Insania, 2014)
Character development in view of Islam is not a new thing even though it may differ from the terms and substance popularized by the people in the western world, and Islam as Rahmatan Lil Alamin Contributions are also connected with the science of Tafsir and Hadith sciences in National Character Development. Quran and Hadith as the primary source of Islamic teachings popularized by Sheikh Yusuf Qaradawi as an attempt to restore / re-open the door / the concept of ijtihad never old-fashioned vacuum caused by many factors, among others, the followers of the school of many who do not understand that the practice of priests mazahib was just the result of their understanding of the verses and the Sunnah of the Prophet.